Equal channel angular extrusion (ECAE) of intermetallics - Anumalasetty Venkata Nagasekhar (2008)
Various techniques of severe plastic deformation (SPD) are used with the purpose of fabricating bulk ultrafine grain materials and for the compaction of advanced powders. Equal channel angular extrusion/pressing (ECAE/ECAP), which is one of the SPD techniques, has unique ability to generate huge strains, high strain rates, absence of shape change, and minimal load requirements. ECAE has thus been used for enhancing the microstructure and mechanical properties of tubular materials as well as for compaction of powders through the powder in tube (PIT) technique. Compared to the conventional metal forming techniques like extrusion, rolling and drawing, this process has many advantages: unidirectional deformations can be produced under relatively low pressures and loads in massive products, and it also promotes the formation of equi-axed grains with high-angle grain boundaries.